Luz e trevas: a ambiguidade na Parábola do Semeador, a partir dos critérios de literalidade da Igreja Católica tradicional, em diálogo com a literariedade - Araujo, Maria Claudia (2014)
We investigate the ambiguity in the Parable of the Sower and the phenomenon of literariness, which comes from the Russian Formalism, since the evangelical discourse of Jesus is poetic and in this parable points to the polyphony to dialogism and intertextuality. We refer to the Hermeneutics of the Work of Art, Gadamer (2010), to rehabilitate the authority of tradition. In the case of the Catholic Church, only because it preserves an ancient exegesis. The corpus adopted in this research is the synoptic narrative of St. Mark (4, 1-20), St. Matthew (13, 1-23) and Luke (8, 4-15), which speaks to Saint John (21, 1 -14) and nuances of the Eternal Church of Apocalypse (21 e 22). The synoptic gospels are considered immanent, by tradition, and of St. John, transcendent. The four plots in the parable of the sowing point to the glory of the Eternal Church and its relationship with Christ, who is also the Sower, as this parable is centered in Christ, as well as its structure, reconstructed here under the support of methodologies of the theory literature. Indeed, Christ, Church, Word and Kingdom of Heaven turn to themselves in this parable - which gives it a jakobsoniana reading the poetic function of language, as well as metalinguistic. Indeed, this innovative interpretation culminates in a new exegetical method, the poetic-religious, specifically designed for reading the Parable of the Sower but that may be developed by traditional exegesis in future from new canonical guidelines and assumptions